Effectiveness of an education intervention on Hepatitis C treatment adherence among Libyan patients in a medical center in Tripoli - Adam, Samia Ibrahim Mohamed (2018)
Hepatitis C infection is a communicable disease caused by hepatitis C virus (HCV). The standard treatment of HCV infection is a combination of Ribavirin (RBV) and Pegylated interferon (PegIFN) for six months or one year. The long duration and the side effects of dual treatment have an enormous impact on patients’ treatment adherence and health-related quality of life (HRQL). This study aims to evaluate the effectiveness of an education intervention to improve treatment adherence as its primary outcome and to improve secondary outcomes including knowledge, general self-efficacy (GSE), virological response, physical components score (PCS), and mental components score (MCS) of HRQL. A single-blind, randomized controlled trial was conducted among 103 patients in Tripoli Medical Center, Libya. The patients who were undergoing treatment with PegIFN and RBV randomly allocated by concealment block randomization, 51 patients to the intervention group and 52 patients to the control group. The intervention group received educational material consisted of a one-day session of PowerPoint presentation, booklet, discussion, and demonstration of PegIFN injection and muscle exercise. The control group received the same educational material at the end of the study. Reliable and valid Arabic questionnaires were used to collect the data at baseline, 3-months, and 6-months post-intervention. The questionnaires were collected information about socio-demographic factors, treatment adherence, knowledge of HCV, self-efficacy, HRQL, and social support. The data was analyzed using SPSS version 22. Generalized Estimating Equation (GEE) was applied to assess the effectiveness of the educational intervention. The findings showed no significant difference between the intervention group and the control group at baseline regarding the primary outcome, secondary outcomes, sociodemographic, social support, and medical history variables. Post-intervention, the GEE results (between the groups) demonstrated significantly higher changes in RBV, PegIFN, and total treatment adherence for the intervention group than the control group. The adjusted odds ratio (AOR) for RBV, PegIFN, and total treatment adherence were 2.639 (95% CI: 1.305, 5.335), 2.458 (95% CI: 1.175, 5.144), and 3.234 (95% CI: 1.621, 6.452), respectively. However, there were no significant changes within the intervention group over time. For secondary outcomes, the GEE results between the groups (overall from baseline to 6-months) showed significantly higher changes for the intervention group than the control group, such as: for a virologic response, the AOR was 2.473 (95% CI: 1.111, 5.505). For hepatitis C knowledge, the AOR was 4.894 (95% CI: 2.842, 8.429). The AOR of GSE was 3.661 (95% CI: 1.233, 10.873). For PCS and MCS of HRQL, the AOR was 15.642 (95% of CI: 4.786, 51.118) and 25.662 (95% CI: 5.514, 119.434), respectively. The GEE results within the intervention group revealed significant changes (p<0.001) for the virologic response, hepatitis C knowledge, and GSE at 3- months and 6-months, but for MCS at 3-month only. These results provide evidence of the effectiveness of the educational intervention to sustain treatment adherence and HRQL and to improve HCV knowledge and self-efficacy.